Semen variables of sheep (Ovis aries) experimentally infected with Toxoplasma gondii - Lopes, W. D. Z.; Costa, A. J.; Souza, F. A.; Rodrigues, J. D. F.; Costa, G. H. N.; Soares, V. E.; Silva, G. S. (Elsevier, 2009)
The influence of Toxoplasma gondii on semen variables and sperm morphology of sheep was evaluated in eight reproductive males distributed into three experimental groups: GI, three sheep inoculated with 2.0 × 105 of P strain oocytes; GII, three sheep infected with 1.0 × 106 of RH strain tachyzoites and; GIII two control sheep. Clinical (rectal temperature, cardiac and respiratory frequencies), parasite and serology exams (IIF) were realized. Sperm variables (volume, motility, vigor and concentration) and semen morphology for each sheep were also evaluated. Thus, semen and blood collections were assessed on post-inoculation days (PIDs)-1,3,5,7,11,14 and weekly thereafter up to PID 70. Clinical alterations were observed (hypothermia and anorexia) in infected sheep from groups GI and GII. Parasitic outbreaks were detected in five sheep. All the infected sheep produced antibodies against T. gondii from PID 5 onwards, reaching a peak of 4096 and 8192 for group GI and GII sheep, respectively. Differences (P < 0.05) were observed regarding the ejaculate volume between the inoculated groups (oocytes and tachyzoites) and control. Even though experimental toxoplasmic infection resulted in clinical symptomology in the inoculated sheep, the minimal alterations in sperm pathologies could not be directly attributed to T. gondii. © 2008 Elsevier B.V. All rights reserved.
Keywords: Semen variables; Sheep-semen; Toxoplasmosis; protozoon antibody; animal; animal disease; blood; body temperature; breathing; growth, development and aging; heart rate; male; parasitemia; parasitology; pathology; pathophysiology; sheep; sheep disease; spermatozoon; spermatozoon count; spermatozoon motility; Toxoplasma; toxoplasmosis; Animals; Antibodies, Protozoan; Body Temperature; Heart Rate; Male; Parasitemia; Respiration; Sheep; Sheep Diseases; Sperm Count; Sperm Motility; Spermatozoa; Toxoplasmosis, Animal; Ovis aries; Toxoplasma gondii